MODEL KEPEMIMPINAN KEPALA MADRASAH IBTIDAIYAH NEGERI DAN SWASTA DI KABUPATEN BANYUMAS - DHARIN, ABU (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
This study aims to assess the implementation of leadership models MIN Head Elementary School in Purwokerto, MI Maarif NU 01 Pageraji and MIM Karanglewas Kidul in the development of the quality of institutions. The method used in this study descriptive qualitative research. The results show that: the model be applicable each of the three different Madrasah adapted to climaticconditions and madrassas that are influenced by the lead figure / head of school.